A Book in four Languages : English - Spanish - French - Mandarin My Animals - Broderick, Kathy; Dresen, Kris; Jiang, Muyun; Luc, Elisabeth; de Alba, Arlette (Chicago, USA Sunbird Books, 2021)
Learn 10 animal words in English, Spanish, French, and Mandarin as you meet some popular pets!
Linguistic Notions
Keywords: Language and Languages